Toxoplasmosis - Akyar, Isın (IntechOpen, 2017)
Toxoplasma gondii was first identified more than 100 years ago in the tissues of birds and mammals. Although toxoplasmosis is important all over the world, its approaches to diagnostic strategies considerably differ among countries. Its wide distribution may be attributed to complex transmission patterns and parasite coevolution with multiple hosts. Although T. gondii infections of immunocompetent people are generally considered asymptomatic, infections in immunocompromised individuals, such as those with AIDS or organ transplant recipients, can result in severe consequences. This book, composed of a series of articles, including effective diagnosis of laboratory in toxoplasma infections, congenital toxoplasmosis, relationship between toxoplasmosis and public health genomics, prevalence, genetic diversity of toxoplasmosis, and microparticle vaccines against Toxoplasma gondii by authors from all over the world, presents a wide open point of view for toxoplasmosis.